Methods Of Teaching Students To Think Critically In Literature Lessons (Journal of Pedagogical Inventions and Practices, 2024)
Critical thinking means independent thinking. In critical thinking, the reader reacts by fully realizing reality and analyzing it in his thinking. In today's Information Age, free and critical thinking is becoming more important than ever. This article focused on the methods of teaching students to think critically in literature classes.